A Fluorescent Biofunctional DNA Hydrogel Prepared by Enzymatic Polymerization. Issue 5 (27th December 2017) - Geng, Jinhui; Yao, Chi; Kou, Xiaohong; Tang, Jianpu; Luo, Dan; Yang, Dayong
Abstract: DNA has arisen as a promising building material for the construction of hydrogels owing to its unique properties such as designability and biocompatibility. All‐DNA hydrogels with only DNA molecules may have limited applications; hence a composite DNA hydrogel with multifunctional moieties is highly desired to cater for specific applications. Herein, a multifunctional DNA hydrogel is created by incorporating DNA with silver nanoclusters (AgNCs), in which AgNCs render the hydrogel simultaneously with fluorescent and antibacterial functions. A circular DNA is rationally designed, which allows for the elongation of DNA chain via an enzymatic polymerization as well as the formation of AgNCs onto DNA scaffolds. The resultant hybrid DNA hydrogel not only shows distinctive morphology and mechanical properties, but also exhibits fluorescent and antibacterial functions. These characteristics, along with its biocompatibility, will allow the hydrogel to be suitable for a variety of potential biomedical applications such as tissue engineering, wound dressing, biosensing, and bioimaging. Abstract : A hybrid multifunctional DNA hydrogel constructed by enzymatic polymerization is reported. A circular DNA is rationally designed, which simultaneously allows for the elongation of DNA chain and the formation of silver nanoclusters onto DNA. The resultant hybrid DNA hydrogel not only shows distinctive morphology and mechanical properties, but also exhibits fluorescent and antibacterial functions.